The Study of Linear Elastic Fracture Mechanics (LEFM) in Fracture - Muhd Hafiz B Hilmi, Muhd Hafiz (Universiti Teknologi Petronas, 2008)
The Linear Elastic Fracture Mechanics (LEFM) in Fracture Mechanics is very important to analyze the structural integrity and predicting the structural behavior of the cracked structure. The most important parameter in Fracture Mechanics is to evaluate the structural integrity is the Stress Intensity factor, K. There are 3 main modes in determining the Stress Intensity Factor which is Modes I, II and III. The K characterizes the stress field in the neighborhood of crack tip when the crack is under tension and to determine whether the crack is stable or unstable. There are established analytical expressions for a simple crack configuration in fracture mechanics book, which can be used to determine K1 value but for the complex geometry configuration, no particular book exist to determine the analytical expression for that particular geometry. Therefore experiment has to be done to determine the analytical expression for the particular geometry configuration. The latest method to determine the Stress Intensity Factor is Finite Element Method by using Finite Element Analysis software package. To enable the software to analyze and produce the Stress Intensity factor value for a specific configuration, the structure has to be modeled followed by meshing procedure and definition of boundary condition in order to get the precise value. Basically this project is only valid for isotropic material.